PENERAPAN METODE ACTIVITY BASED COSTING DALAM PENENTUAN HARGA POKOK PRODUKSI PADA PT. SARIMELATI KENCANA (PIZZA HUT MANADO TOWN SQUARE) - Pelleng, Stephany Ch.; Karamoy, Herman; Tirajoh, Victorina (Universitas Sam Ratulangi, 2013)
Nowadays, every company has to have a right and efficient way to know their own pricing process. The better the company count it, the better it would be to compete in the market because the right method or system will decrease the cost and increase the profit. Activity Based Costing System is a method of calculating the cost of goods manufactured based on activities in a company using more cost driver, so it can calculate more accurate. This method is expected to be applied to the PT. Sarimelati Kencana who still using the traditional system for calculating the cost of goods manufactured. This research has a purpose to know the cost of goods manufactured in the company using activity based costing system. There are qualitative and quantitative data on this project. Qualitative data for company profile and quantitative data for production costs. This is descriptive research and the result shows that the pricing process using ABC method give overcost condition for pizza hut personal and undercost condition for pizza hut regular and large.